Sistem Informasi Indeks Kepuasan Perpustakaan Vidhya Tama Berbasis Web di SMP Negeri 2 Kudus - Majid, Akmal Abdul; Arifin, Muhammad (Al-DYAS, 2026)
Although the measurement of library service satisfaction indices has been widely discussed, the implementation of web-based satisfaction index information systems at the school level, where manual methods are still used, has rarely been examined. This study aims to assess the effectiveness of a web-based library satisfaction index information system at Perpustakaan Vidyatama SMP Negeri 2 Kudus in improving the efficiency of data collection, the accuracy of score processing, and the quality of reporting. The research adopts the waterfall development model, encompassing the stages of needs analysis, design, implementation, and testing. Data were obtained through observation of manual survey processes, interviews with librarians, and system trials. The system was developed using Laravel and MySQL, and includes features for online survey completion, automatic index calculation using weighted averages, and the presentation of informative reports. The findings show increased speed of recap processes, reduced risk of data loss, and improved accuracy of survey results. These results underscore the importance of library service digitalization and demonstrate that a web-based satisfaction index information system can serve as an effective solution for improving service evaluation processes, while also providing a practical reference for other schools wishing to adopt similar satisfaction evaluation systems.